Iftar preparation – It’s a UMP tradition! - UMP, PNC (2018)
Universiti Malaysia Pahang (UMP) still maintains its Ramadhan tradition of preparing iftar together and offering them in huge trays for free to its staff and students who are breaking their fast at UMP mosques in Gambang and Pekan campus respectively. That particular memory will surely be etched forever in the minds of the alumni of the university during Ramadhan.